2009
DOI: 10.1891/0886-6708.24.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Judgments of a Sexual Assault Scenario: The Role of Prejudicial Attitudes and Victim Weight

Abstract: One potential barrier facing sexual assault survivors is that prejudicial attitudes and perceptions of victim appearance can influence the amount of blame, sympathy, and help that they receive from others. Using Weiner's (1980) attribution-affect-action theory as a guide, the present study investigated the relation between observer attitudinal characteristics (rape myth acceptance [RMA] and antifat attitudes [AFA]), victim weight, and specific judgments regarding a hypothetical sexual assault case. Female unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 0 publications
8
45
0
Order By: Relevance
“…Although the study yielded several novel findings, we must also acknowledge that we did not take the victim’s attractiveness or status into account. Given that researchers have been interested in the impact of victim appearance in rape cases (e.g., Clarke & Lawson, 2009; Deitz, Littman, & Bentley, 1984), the obvious next step is to incorporate the victim’s perceived desirability. Relatedly, because we incorporated both the physical attractiveness and occupation (status) within the defendant desirability manipulation, we cannot conclude that the desirability effects are stronger for attractiveness versus status.…”
Section: Discussionmentioning
confidence: 99%
“…Although the study yielded several novel findings, we must also acknowledge that we did not take the victim’s attractiveness or status into account. Given that researchers have been interested in the impact of victim appearance in rape cases (e.g., Clarke & Lawson, 2009; Deitz, Littman, & Bentley, 1984), the obvious next step is to incorporate the victim’s perceived desirability. Relatedly, because we incorporated both the physical attractiveness and occupation (status) within the defendant desirability manipulation, we cannot conclude that the desirability effects are stronger for attractiveness versus status.…”
Section: Discussionmentioning
confidence: 99%
“…Research on rape myth acceptance and the attribution of blame in rape scenarios can be loosely divided, based on the variables of interest, into three meaningful categories: (a) victim characteristics (e.g., Davies & Rogers, 2006; Grubb & Turner, 2012), (b) perpetrator characteristics (e.g., Bell, Kuriloff, & Lottes, 1994; Clarke & Lawson, 2009), and (c) observer characteristics (e.g., van der Bruggen & Grubb, 2014; White & Kurpius, 2002). We will discuss research regarding each of these categories in turn.…”
Section: Sexual Assault Vignette Researchmentioning
confidence: 99%
“…First, characteristics of the victim, including gender, adherence to traditional gender roles, alcohol use, and appearance (including weight, attractiveness, and attire), all influence the amount of blame that victim receives (Clarke & Lawson, 2009; Davies & Rogers, 2006; Davies, Rogers, & Whitelegg, 2009; Davies, Smith, & Rogers, 2009; Deitz, Littman, & Bentley, 1984; Grubb & Turner, 2012; Howard, 2003; Kelly, 2009; Maurer & Robinson, 2008; van der Bruggen & Grubb, 2014; Wakelin & Long, 2003; Workman & Freeburg, 1999). Importantly for this project, there is also research on the effect of the victim’s sexuality.…”
Section: Sexual Assault Vignette Researchmentioning
confidence: 99%
“…There are few studies that have investigated the effects of obesity on secondary victimization. For instance, researchers found that the effects of rape myth acceptance and anti-fat attitudes influence others' attitudes toward rape victims (Clarke & Lawson, 2009;Clarke & Stermac, 2011). They found that participants rated the victim more negatively and the perpetrator more positively when the victim was obese verses thin.…”
Section: Introductionmentioning
confidence: 99%